A multi-locus analysis of Arabic negation : micro-variation in Southern Levantine, Gulf and Standard Arabic - Alqassas, Ahmad, 1982- (Edinburgh studies in theoretical linguistics., 2019)
Studying the micro-variation in the syntax of negation of Southern Levantine, Gulf and Standard Arabic, this text includes new and recently published data that support key issues for the syntax of negation, challenging the standard parametric view that negation has a fixed parametrized position in syntactic structure.